ANALISIS KEHANDALAN PNEUMATIC SYSTEM PADA PESAWAT PENUMPANG DI PT ABC - Kusnanto, Kusnanto; Sugianto, Welly (LPPM Universitas Putera Batam, 2021)
Unscheduled removal is the replacement of components outside of the scheduled component replacement package due to a failure finding found outside the scheduled component replacement package. Ineffective maintenance planning can result in cost losses for airlines because unscheduled component replacement planning has not been carried out in accordance with the process suggested by the literature so it is not effective. This ineffectiveness can cause delays in the treatment process. Therefore, this study aims to provide preventive maintenance recommendations for the autobrake system components.The repair of unscheduled component replacement planning is carried out using the Reliability Centered Maintenance (RCM) method. First, knowing the function, failure mode, and failure effect of the system using FMECA. Second, determine the level of risk of failure of these components using the Risk Priority Number (RPN) based on the results of the pareto reliability report and the results of FMECA. Third, determine the treatment time interval using the weibull distribution. Fourth, provide types of recommendations on components to prevent unscheduled removal.The results of this evaluation and analysis are used as input in the recommendations for the preparation of a new planning process. In the new planning process it is recommended to add inspections to the High Pressure Valve component at 8,684 FH, the Pressure Regulating Valve at 8,018 FH and the Thermostat at 10,007 FH.